Effect of Hydrochloric Acid, Mechanical Scarification, Wet Heat Treatment on Germination of Seed of Parkia Biglobosa African Locust Bean (Daurawa) Case Study of Gombe Local Government Area - Z Abubakar; A Maimuna (Journal of Applied Sciences and Environmental Management)
The effect of different treatments of breaking seed dormancy of Parkia biglobosa seeds were studied in botanical garden of Biological Sciences Department, Gombe State University in May ,2011, the response of different treatments observed showed 100% for wet heat, 90% for scarification (sand paper) and 70% for HCL of 50% concentration while the untreated seed control is 60% germination respectively and the data collected when subjected to analysis of variance showed significant differences between the treatments, the leaves and seedling height performed better than the control(untreated seeds), wet heat, mechanical scarification and 50% hydrochloric acid were found to induce germination of the dormant seeds of Parkia biglobosa These methods could be applied to raise seedlings of plant for field propagation and afforestation programme.